Cognitive training interventions in children: contributions from a developmental diversity view. - Giovannetti, Federico (Apuntes de Psicología, 2022)
In the last decades, there has been a flourishing interest in the design of cognitive training interventions aimed to promote executive and self-regulatory development in children. However, evidence suggests that the aims of the studies are not always achieved. The present work proposes to analyze the discourses that ground the design and implementation of cognitive training interventions in order to avoid normative views of cognitive development. In addition, this work proposes to approach some of the problems of the area from a relational view, understanding development in a complex and diverse way. Finally, some possible future approaches and directions will be addressed.